The Action of Red Cell Calcium Ions on Human Erythrophagocytosis in Vitro - Romero, Pedro J.; Hernández-Chinea, Concepción (Frontiers in Physiology, 2017)
In the present work we have studied in vitro the effect of increasing red cell Ca2+ ions on human erythrophagocytosis by peripheral monocyte-derived autologous macrophages. In addition, the relative contribution to phagocytosis of phosphatidylserine exposure, autologous IgG binding, complement deposition and Gárdos channel activity was also investigated. Monocytes were obtained after ficoll-hypaque fractionation and induced to transform by adherence to glass coverslips, for 24 h at 37°C in a RPMI medium, containing 10% fetal calf serum. Red blood cells were loaded with Ca2+ using 10 µM A23187 and 1 mM Ca-EGTA buffers, in the absence of Mg2+. Ca2+-loaded cells were transferred to above coverslips and incubated for 2 h at 37°C under various experimental conditions, after which phagocytosis was assessed by light microscopy. Confirming earlier findings, phagocytosis depended on internal Ca2+. Accordingly; it was linearly raised from about 2 to 15% by increasing the free Ca2+ content of the loading solution from 0.5 to 20 µM, respectively. Such a linear increase was virtually doubled by the presence of 40% autologous serum. At 7 µM Ca2+, the phagocytosis degree attained with serum was practically equal to that obtained with either 2 mg/ml affinity-purified IgG or 40% IgG-depleted serum. However, phagocytosis was reduced to levels found with Ca2+ alone when IgG-depleted serum was inactivated by heat, implying an involvement of complement. On the other hand, phagocytosis in the absence of serum was markedly reduced by preincubating macrophages with phosphatidylserine-containing liposomes. In contrast, a similar incubation in the presence of serum affected it partially whereas employing liposomes made only of phosphatidylcholine essentially had no effect. Significantly, the Gárdos channel inhibitors clotrimazole (2 µM) and TRAM-34 (100 nM) fully blocked serum-dependent phagocytosis. These findings show that a raised internal Ca2+ promotes erythrophagocytosis by independently triggering phosphatidylserine externalization, complement deposition and IgG binding. Serum appeared to stimulate phagocytosis in a way dependent on Gárdos activity. It seems likely that Ca2+ promoted IgG-binding to erythrocytes via Gárdos channel activation. This can be an important signal for clearance of senescent human erythrocytes under physiological conditions.